Effect of Basic Socialization to Attitudes and Value of Java’s Culture to Woman’s Career Development - Alifiulahtin Utaminingsih (Wacana Journal of Social and Humanity Studies, 2018)
This research is aimed to fight for gender equality in government bureaucracy, and also supporting and barrier factors related about career development female staff  in Social Departement of Malang. The used is gender theory and career development by Jeanne Marie Col, this is focused on basic socialization to attitudes and value. Research method is a descriptive qualitative. This result showing that lower level of career development of female staff who had structural  job is good. There are two things that affecting female motivation level to develop their career. Those factors are subjective internal and external factor. Internal factor is female staff tend to have high motivation and confident about their ability. The external factors are family and working environment: (a) Family, female is demanded to domestic and public role in the same time (a good multiple roles). That roles  affect into career development motivation in reaching a higher position; (b) Working environment, there is a common culture where the female staff does want to achieve higher position.